2012
DOI: 10.1364/oe.20.006204
|View full text |Cite
|
Sign up to set email alerts
|

Four-wave-mixing between the upper excited states in a ladder-type atomic configuration

Abstract: Four-wave-mixing (FWM) radiation is generated between the hyperfine structures of the 5D and 5P states in a thermally broadened rubidium atomic vapor using resonant atomic coherence. Background-free unidirectional signals having narrow spectral linewidths are isolated and experimentally studied in the frequency domain, and the effects of the driving beam parameters on the properties of the radiation are discussed. The radiation has several new properties compared to traditional FWM radiations generated between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The two-photon coherence terms for the constituent systems, i.e., Ξ and Λ are ρ 14 and ρ 23 , respectively. In this system, three optical fields trigger FWM due to the third order nonlinearity of the medium in a direction driven by the phase-matching condition [19,21]. Twophoton coherence for the Ξ system is imperative to observe three-photon coherence on applying the drive field Ω d [19].…”
Section: Steady State Solution Under Weak Probe Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…The two-photon coherence terms for the constituent systems, i.e., Ξ and Λ are ρ 14 and ρ 23 , respectively. In this system, three optical fields trigger FWM due to the third order nonlinearity of the medium in a direction driven by the phase-matching condition [19,21]. Twophoton coherence for the Ξ system is imperative to observe three-photon coherence on applying the drive field Ω d [19].…”
Section: Steady State Solution Under Weak Probe Approximationmentioning
confidence: 99%
“…In multilevel atomic systems, the interference and coherence are also utilized to elucidate nonlinear wave mixing. In four-level atomic systems, various studies have observed three-photon electromagnetically induced absorption (TPEIA) and FWM simultaneously [19][20][21]. In a ladder-type atomic system conversion of TPA and EIT to TPEIA was demonstrated [22] and conditions for observing three-photon coherence in a Ξ system were also reported [23].…”
Section: Introductionmentioning
confidence: 99%
“…The suppression and enhancement of four-wave-mixing (FWM) process in electromagnetically induced transparency (EIT) windows [1][2][3][4][5][6][7][8] can be implemented in many multi-level systems, such as ladder-type, [2,9,10] Y-type, [8] and double lambda-type [4][5][6][11][12][13] level configurations. In a ladder-type system with hyperfine ground states, the magnitude of FWM signal is found to be dependent on the transition route, and dominantly related to the residual two-photon coherence according to the degree of optical pumping to the other ground state.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished by non-linear frequency conversion in the four-wave mixing (4WM) process using strong resonant non-linearities in atoms thanks to transitions between excited states. Such processes have been used to demonstrate frequency conversion in rubidium [7][8][9][10][11] or to generate photon pairs in the cascaded spontaneous 4WM process [12][13][14]. Multiphoton processes are also a developing method to interface light and Rydberg atoms [15][16][17].…”
Section: Introductionmentioning
confidence: 99%